Pyrolysis of Cedrus deodara saw mill shavings in hydrogen and nitrogen atmosphere for the production of bio-oil. (December 2016) - Krishna, Bhavya B.; Biswas, Bijoy; Ohri, Priyanka; Kumar, Jitendra; Singh, Rawel; Bhaskar, Thallada
Abstract: Pyrolysis of deodar has been carried out at 350 and 400 °C at 0.1, 1, 2 and 3 MPa hydrogen pressure. Pyrolysis under nitrogen atmosphere has been carried out at 300, 350, 400 and 450 °C. The favourable process conditions under hydrogen environment were found to be 400 °C and 2 MPa pressure and in case of nitrogen environment was found to be 350 °C. The products have been characterised using GC–MS, 1 H NMR, FT-IR and SEM. It has been observed that the bio-oil is rich in phenolic compounds under nitrogen and hydrogen atmospheres. Selectivity towards certain compounds such as catechol, vanillin and its derivatives etc. are high under hydrogen atmosphere. Deodar has undergone decomposition significantly which is evident by the absence of most functionality in bio-char and loss of crystallinity. The products formed under hydrogen and nitrogen environments are different from each other owing to the differences in reaction mechanism. Highlights: Favourable conditions for deodar pyrolysis in hydrogen are 400 °C, 2 MPa. In case of nitrogen atmosphere, maximum bio-oil yield was obtained at 350 °C. Bio-oil was majorly composed of phenolic compounds and aromatic ethers. Bio-char was devoid of functionalities indicating complete conversion.